2014
DOI: 10.1371/journal.ppat.1004276
|View full text |Cite|
|
Sign up to set email alerts
|

Syk Signaling in Dendritic Cells Orchestrates Innate Resistance to Systemic Fungal Infection

Abstract: Host protection from fungal infection is thought to ensue in part from the activity of Syk-coupled C-type lectin receptors and MyD88-coupled toll-like receptors in myeloid cells, including neutrophils, macrophages and dendritic cells (DCs). Given the multitude of cell types and receptors involved, elimination of a single pathway for fungal recognition in a cell type such as DCs, primarily known for their ability to prime T cell responses, would be expected to have little effect on innate resistance to fungal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 87 publications
6
94
2
1
Order By: Relevance
“…Consistent with SYK/CARD9 being central for CLR signal integration, mice with hematopoietic or DC-specific Syk deletion or with global CARD9 deficiency are highly susceptible to C. albicans (29,60) and A. fumigatus (43) challenge. CARD9/SYK-dependent susceptibility maps to defective cytokine responses that control neutrophil, NK, and T cell trafficking or activation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consistent with SYK/CARD9 being central for CLR signal integration, mice with hematopoietic or DC-specific Syk deletion or with global CARD9 deficiency are highly susceptible to C. albicans (29,60) and A. fumigatus (43) challenge. CARD9/SYK-dependent susceptibility maps to defective cytokine responses that control neutrophil, NK, and T cell trafficking or activation.…”
Section: Introductionmentioning
confidence: 86%
“…CARD9/SYK-dependent susceptibility maps to defective cytokine responses that control neutrophil, NK, and T cell trafficking or activation. During systemic candidiasis, DCs secrete IL-23 in a SYK-dependent manner, prompting IL-17A-dependent (hereafter referred to as IL-17) NK cell release of GM-CSF, thereby activating candidacidal neutrophils at infection sites (60,61).…”
Section: Introductionmentioning
confidence: 99%
“…35 Previously, it is a general thought that DCs have little effect on innate resistance to fungal infection. However, a recent study revealed that selective loss of Syk in DCs abrogates innate resistance to acute systemic C. albicans infection in mice, 155 which indicates that a single kinase in DCs might orchestrate a complex series of molecular and cellular events in innate resistance to C. albicans. Actually, full protection against most pathogens requires an adaptive response, which is initiated and directed by DCs.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…Moreover, human NK cells activated by C. albicans can secret GM-CSF, IFN-g, and TNF-a. 140,141 However, previous studies showed that the production of IFN-g by murine NK cells was down-regulated by C. albicans.…”
Section: Natural Killer Cellsmentioning
confidence: 99%